Size at birth and cognitive ability in late life: A systematic review. (13th June 2019) - Krishna, Murali; Jones, Steven; Maden, Michelle; DU, Bharath; MC, Ramya; Kumaran, Kalyanaraman; Karat, Samuel Christraprasad; Fall, Caroline H.D.
Abstract : Introduction: Recent evidence suggests that growth restriction in utero may lead to neurocognitive disorders in late life, either through impaired brain development or adverse metabolic programming. Methods: Systematic review of literature investigating the relationship between size at birth and cognitive abilities in late life. The search, data extraction, and rating for the quality of reporting were conducted independently by two researchers. Results: Of 533 selected studies, 11 were included in this systematic review and 10 of these were from high‐income setting. Of these 11 studies, eight indicated that lower birth weight is a risk factor for lower cognitive function in late life, at least in high‐income countries. The reported effect sizes were small and it was not possible to conduct meta‐analyses because of clinical heterogeneity Discussion: A modest association of lower birth weight with lower cognitive abilities in late life is consistent with persisting effects of the prenatal environment on brain function. As with all observational studies, confounding is an alternative explanation. Further studies are required to elucidate the mechanisms.